V-shaped electro-optic response observed in a chiral ferroelectric smectic liquid crystal - VIJ, JAGDISH; PANARIN, YURI; SONG, JANG-KUN (My University, 2008)
We report on the observation of V-shaped switching in a ferroelectric liquid crystal cell over a wide range of temperatures. Results of the optical transmittance in the visible region give us the helical pitch for various temperatures of the ferroelectric liquid crystalline compound used. We show that the helical pitch, in addition to the spontaneous polarization PS and thickness of the alignment layer of the cell, is an important factor in giving V-shaped switching. A longer or helical compensated mixture gives a better V-shaped switching.
PUBLISHED
Keywords: Electronic & Electrical Engineering